PUBLIC POLITICS OF THE GENERAL OFFICE OF SPORTS AND LEISURE OF THE MUNICIPAL DISTRICT OF PETRÓPOLIS: EVALUATION BY THE EDUCATIONAL SPORT (Fiep Bulletin - online, 2014)
The subject of this study addresses the public politics in the extent of the sport and leisure developed in the Municipal District of Petrópolis.We intend to evaluate the sportive programs developed by the General Office of Sports and Leisure, using as a base the orientative principles of the Educational Sport, contributing to the study in this area.It investigates if the public politics of Educational Sport presents itself in an emancipation way or it converges for the development of a compensatory politics.The hypothesis is based on the fact of most of the sporting programs usually present damaged because of two aspects: one, the government enterprises in the social area have as historical characteristic the administrative discontinuity, causing many programs remaining only short periods corresponding to the current government. This problem comes since long time ago, harming the base development, whereas, when implanting a social program, many times it is extirpated by the following government or even by the current. The other refers to the assistance characteristic of some programs, damaging a real transformation, which could indicate the maintenance of the status quo by the creation of another State control apparatuses through the sporting programs.The methodology follows the qualitative perspective with resource to the descriptive design, where a questionnaire was applied to eleven coordinators of the Program, with seven open subjects.The treatment of the data was based on the speech analysis by Dominique Maingueneau (1997), as well as the theoretical referential in Althusser (1996), Ansart (1978), Badinter (1985), Eliade(1972), Foucault (1977, 1979), Laraia (1988), Ministry of Education and Sport (1996).The results showed the development of a politics that addresses for an emancipation action, looking for the autonomy and possibilities of construction of a history directed to the social inclusion and democratization of the sporting practice.
Keywords: Educational Sports; Sportive Initiation; Emancipation politics